Weight-bearing Ultrasound to Diagnose Talar Dislocation Causing Tarsal Tunnel Syndrome - Duarte, Márcio Luís; da Silva, Mayara Oliveira; Soares, Ocacir de Souza Reis; Moreira, Norma Sueli Albino; Arie, Eduardo Kenzo (Prague medical report, 2024)
The neuropathic compression of the tibial nerve and/or its branches on the medial side of the ankle is called tarsal tunnel syndrome (TTS). Patients with TTS presents pain, paresthesia, hypoesthesia, hyperesthesia, muscle cramps or numbness which affects the sole of the foot, the heel, or both. The clinical diagnosis is challenging because of the fairly non-specific and several symptomatology. We demonstrate a case of TTS caused by medial dislocation of the talar bone on the calcaneus bone impacting the tibial nerve diagnosed only by ultrasound with the patient in the standing position.
Keywords: Tibial nerve; dislokace kloubu; Tarsal tunnel syndrome; syndrom tarzálního tunelu; Ultrasonography; Weight-Bearing; Talus; Nerve compression syndromes; lidé; Diagnosis; zatížení muskuloskeletálního systému; Tarsal Tunnel Syndrome; talus; Humans; Joint Dislocations; ultrasonografie